Secondary Intention Healing Following Surgical Shave Excision of Nevi on the Penis. A Retrospective Study of 8 Cases - Wen G; Hu J; Zhu M; Yao X; Wang X; Mao D (Clinical, Cosmetic and Investigational Dermatology)
Guangdong Wen, Jian Hu, Mengyi Zhu, Xueyan Yao, Xiaojie Wang, Dandan Mao Department of Dermatology, Peking University People’s Hospital, Beijing, People’s Republic of ChinaCorrespondence: Dandan Mao, Department of Dermatology, Peking University People’s Hospital, No. 11 Xizhimen South Street, Beijing, 100044, People’s Republic of China, Tel +86-10-88325472, Email maodandan1992@126.comPurpose: The purpose of the study was to determine the efficacy of secondary intention healing of wounds after penile nevi surgical shave excision.Patients and Methods: A retrospective study in the Department of Dermatology, Peking University People’s Hospital, between 2019 and 2023, on 8 patients with penile nevi was performed. Patients were treated by surgical shave excision and underwent secondary intention healing. For patients with relatively large nevi involving the glans penis, staged excisions were applied.Results: In our case series, 7 patients achieved excellent wound esthetic outcomes and 1 patient achieved a good esthetic outcome, all with no loss of sensation. During the follow-up, 2 patients experienced the recurrence of pigmented macules in situ and received a second excision, achieving satisfactory outcomes as well.Conclusion: Secondary intention healing of wounds after surgical shave excision of penile nevi has satisfactory outcomes and is a simple procedure for both doctors and patients.Keywords: penis, nevus, shave, excision, secondary intention healing